Response and Damage Characteristics of Segmental Tunnel Lining under Various Dynamic Load Conditions - Jinling Chai; Ke Wang; Shihao Wang; Yong Wang; Yi Liu (Advances in Civil Engineering)
This paper investigates segmental lining, developing a numerical model to explore the dynamic interaction between saturated soil and the lining structure, and analyses the effects of the angle of incident load and the wavelength-to-diameter ratio on the displacement, deformation, and distribution of the plastic zone of the structure. The findings demonstrate that the structure experiences vertical compressive deformation during ground shock predominantly. The structure can be categorised into the major deformation region (with an angle within 60° of the vertical direction) and the minor deformation region (with an angle within 30° of the horizontal direction), determined by the structure’s radial deformation. The maximum radial velocity of the nodes in the major deformation area is greater and swifter, whereas the maximum radial velocity of the nodes in the minor deformation region is lesser and mostly equivalent in extent. The maximum radial displacement of the nodes in the major deformation area is highly receptive to the loading wavelength–diameter ratio (L/D) (the ratio of the load wavelength to the structure’s outer diameter) when the wavelength-to-diameter ratio (L/D) is small (1 ≤ L/D ≤ 5). Conversely, the maximum radial displacement in the minor deformation area is considerably sensitive to the wavelength–diameter ratio when 5 ≤ L/D ≤ 30. The total displacement and velocity of the structure remain unaffected by the angle of load incidence. However, it affects the maximum deformation of the structure as well as the location where the maximum node velocity occurs. In addition, the joint surface of the structure experiences the highest plastic strain at an angle of load incidence of 60°.